Nonanatomic and Suture-Based Coracoclavicular Joint Stabilization Techniques Provide Adequate Stability at a Lower Cost of Implants in Biomechanical Studies When Compared With Anatomic Techniques: A Systematic Review and Meta-Analysis - Theodorakys Marín Fermín, M.D; Jean Michel Hovsepian, M.D; Víctor Miguel Rodrigues Fernandes, M.D; Ioannis Terzidis, M.D., B.Sc., Ph.D., F.E.B.S.M; Emmanouil Papakostas, M.D., F.E.B.S.M; Jason Koh, M.D., M.B.A., F.A.A.O.S (Elsevier, 2021)
Purpose: To compare the stability and cost of the used implants in nonanatomic and anatomic acromioclavicular joint repair/reconstruction (ACCR) techniques tested in cadaveric shoulder biomechanical studies during the last decade. Methods: A systematic review and meta-analysis were performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and prospectively registered in PROSPERO. Two independent reviewers searched PubMed, Embase, and Virtual Health Library databases. Studies evaluating 3-direction stability under 70-N loads and load-to-failure protocols with servohydraulic testing systems were included. A meta-analysis of the mean differences of anterior, posterior, and superior direction; relative stability value in 3 directions; superior direction load-to-failure; stability/cost index; and load-to-failure/cost index was performed using a continuous random-effects model and 95% confidence interval. Results: Eighteen articles were included. Both non-ACCR and ACCR techniques exceeded the minimum acceptable threshold of stability and load-to-failure. ACCR techniques were biomechanically better in terms of anterior stability (P = .04) and relative stability value (mean difference 64.08%, P = .015). However, supraphysiological stability and failure loads were achieved with non-ACCR techniques at a lower cost of implants. Techniques combining 2 clavicular tunnels separated by at least 10 mm, a mean of 2 sutures, and/or suture tapes had the greatest stability/cost index and load-to-failure/cost index among the included techniques (confidence interval 99%). Conclusions: Non-ACCR and ACCR techniques exceeded the minimum acceptable threshold of stability and failure loads in controlled biomechanical testing. However, non-ACCR and techniques combining 2 clavicular tunnels separated by at least 10 mm, a mean of 2 sutures, and/or suture tapes provide supraphysiologic stability and failure loads at a lower cost of implants. Clinical Relevance: Non-ACCR and suture-based techniques may provide more cost-effective and greater value treatment for acromioclavicular joint injury and could be considered in the surgical management of normal activity individuals and cost-sensitive populations.